Activated PI3K-δ syndrome presenting with cervical lymphadenopathy in a pediatric patient: a case report and review of the literature - Huang, Zhiwei; Wang, Yaping; Wei, Ruoying; Ding, Hui; Du, Lian; Yang, Xiaomei; Li, Fu (Frontiers in Immunology, 2025)
BackgroundActivated phosphoinositide 3-kinase delta syndrome (APDS) is a primary immunodeficiency caused by gain-of-function mutations in the PIK3CD gene, leading to dysregulated immune responses. Clinical manifestations include recurrent infections, lymphoproliferation, and increased risk of malignancies. Due to its rarity and variable presentation, APDS is often misdiagnosed or diagnosed late.Case presentationWe report a case of a 12-year-old girl presenting with persistent cervical lymphadenopathy. Imaging studies revealed extensive lymph node involvement and splenomegaly. PET-CT raised suspicion for lymphoma. Histopathology of the excised lymph node demonstrated Epstein-Barr virus (EBV) latent infection Type III, while whole exome sequencing identified a pathogenic PIK3CD c.3061G>A (p.Glu1021Lys) heterozygous variant. This confirmed the diagnosis of APDS. Targeted therapy with sirolimus was initiated, leading to significant regression of lymphadenopathy and splenomegaly. The patient maintained good clinical status during follow-up.ConclusionThis case highlights the importance of genetic testing in pediatric patients with lymphoproliferative disease and unusual infection patterns. Early diagnosis of APDS enables personalized, targeted treatment and avoids overtreatment with cytotoxic agents.